Anomalous Course of the Internal Carotid Artery Resulting in Optic Nerve Compression - Vance Taylor, Danielle; Cappelli, Rena; Wiedemann, Leah (Canadian Journal of Optometry, 2021)
Compression of the optic nerve by the internal carotid artery can occur due to their proximity as they exit the cavernous sinus. This report details a case of unilateral compressive optic neuropathy resulting from an anomalous course of the internal carotid artery. It presents optical coherence tomography scans, Humphrey visual field results, and magnetic resonance images, as well as reviews other causes of optic neuropathy that can have a similar clinical presentation.